Occupational risk involving students of health - Éder Oliveira Rocha; Amanda Mendonça Marques; Luana Kelle Batista Moura; Cristina Maria Miranda de Sousa; Eucário Leite Monteiro Alves; Gerardo Vasconcelos Mesquita (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: To analyze the social representations of occupational risks involving students in the area of health. Method: Exploratory research with 160 students from nursing, medicine and dentistry, through interviews. The data were processed in ALCESTE 4.8 and lexical analysis done by descending hierarchical classification. Results: In four semantic classes, namely: occupational risks involving students in the area of health, the work environment and occupational risks, exposure to accidents with sharps and adoption of standard precautions as biosecurity measures. Conclusion: Students healthcare represent occupational risks, such as a concern for the prevention of cross infection in the workplace, should both professionals and students of health, adopt standard precautions and biosecurity measures in the environment work.